Attitudes and Motivations Toward Craft Beer Consumption: An Explanatory Study in Two Different Countries. Issue 3 (24th March 2019) - Rivaroli, Sergio; Lindenmeier, Jörg; Spadoni, Roberta
ABSTRACT: This study adopts a revised model of the Theory of Planned Behaviour incorporating self-identity and desire for unique consumer products to understand and predict consumers' motivation to drink craft beer in Germany (N=210) and Italy (N=211). Data were analysed using Partial Least Squares modelling (PLS) approach. The findings provide support that the extended TPB model is a useful tool for understanding the consumers' choice to drink craft beer. The results confirm the major role played by consumers' attitudes and self-identity. Mediation analysis indicates a potential indirect effect from self-identity, subjective norms and the desire for unique consumer products on individual behaviour both in the German and Italian sample. Implications for theory are discussed for further research developments within the context of consumption of crafted food products.